Exploring wild Aspleniaceae ferns as safety sources of polyphenols: The case of Asplenium trichomanes L. and Ceterach officinarum Willd. - Farràs, Adrià; Mitjans, Montserrat; Maggi, Filippo; Caprioli, Giovanni; Vinardell, María Pilar; López, Víctor (Frontiers in Nutrition, 2022)
The forest ecosystem is a source of material resources used since ancient times by mankind. Ferns are part of different oriental systems of traditional medicine due to the phytochemical variety of their fronds, which has allowed their traditional use to be validated through ethnopharmacological studies. In Europe, different cultures have used the same fern with a wide variety of applications due to its presence in most European forests. In recent years, studies on the phytocharacterization and biological activity of the fronds of the main European ferns have been published. In this study, the presence of polyphenolic phytochemicals has been evaluated by HPLC-MS/MS in the fronds of two wild ferns together with in vitro activities in non-tumoral and human tumoral cell lines. The polyphenols were extracted from Asplenium trichomanes L. and Ceterach officinarum Willd. by cold maceration using methanol. The main phytochemicals of polyphenolic origin in the extracts of A. trichomanes and C. officinarum determined by HPLC-MS/MS were the flavonol hyperoside and the phenolic acid chlorogenic acid, respectively. This different polyphenolic nature of both extracts contributes to the divergence of the behaviour experienced in the biological activities tested, but none of the extracts showed a cytotoxic or phototoxic profile in the different tested cell lines. However, the cytoprotective values front the H2O2 oxidative stress induced in the 3T3 and HaCaT cell lines position these extracts as possible candidates for future health applications.